Investigating the role of hydrological connectivity on the processing of organic carbon in tropical aquatic ecosystems - Pereira, Ryan; Panizzo, Virginia N.; Bischoff, Juliane; McGowan, Suzanne; Lacey, Jack; Moorhouse, Heather; Zelani, Noor Suhailis; Ruslan, Muhammad Shafiq; Fazry, Shazrul (Frontiers in Earth Science, 2024)
Inland waters are highways of carbon and nutrient flows between the land and ocean. Aquatic environments integrate multiple sources and processes over space and time that influence ecosystem functionality. The complexity of these systems and their multiple interactions with the surrounding environment are conceptualised, but often lack empirical scrutiny that allows further understanding of how inland waters mobilise, transport, and utilise carbon and nutrients. This is particularly evident in tropical waters. Here, we apply advanced geochemical analyses of dissolved organic matter (DOM) composition in conjunction with algal pigment biomarkers, to determine the seasonal variability of organic matter production, processing and export for a tropical, floodpulse wetland, Tasik Chini (Malaysia). We identify two phases in the hydrological cycle: Phase 1 signifying a transition from the wet season with high suspended sediment and dissolved organic carbon concentrations. DOM is composed of humic substances, building blocks and lower molecular weight compounds. Towards the end this phase then are periods of increased water clarity and algal productivity. This is followed by Phase 2, which has a greater contribution of autochthonous DOM, composed of proteinaceous material, concomitant with lower dissolved nutrient concentrations, increased mixotrophic algae and emergent vegetation. Based on this framework, we highlight the role of such tropical wetland lakes as hydrological “bottlenecks,” through a lentic/lotic switch that shifts aquatic transport of carbon and nutrients from lateral river continuum supply to flood pulses. We highlight the need to consider inherent biases of spatial and temporal scaling when examining freshwater ecosystems along the land-ocean aquatic continuum.